Intratumoral tertiary lymphoid organ is a favourable prognosticator in patients with pancreatic cancer - Hiraoka, N (Br J Cancer, 2015)
BACKGROUND: Host immunity has critical roles in tumour surveillance. Tertiary lymphoid organs (TLOs) are induced in various inflamed tissues. The aim of this study was to investigate the clinicopathological and pathobiological characteristics of tumour microenvironment in pancreatic ductal carcinoma (PDC) with TLOs. METHODS: We examined 534 PDCs to investigate the clinicopathological impact of TLOs and their association with tumour-infiltrating immune cells, the cytokine milieu, and tissue characteristics. RESULTS: There were two different localisations of PDC-associated TLOs, intratumoral and peritumoral. A better outcome was observed in patients with intratumoral TLOs, and this was independent of other survival factors. The PDC tissues with intratumoral TLOs showed significantly higher infiltration of T and B cells and lower infiltration of immunosuppressive cells, as well as significantly higher expression of Th1- and Th17-related genes. Tertiary lymphoid organs developed with an association with arterioles, venules, and nerves. These structures were reduced in an association with cancer invasion in PDC tissues, except for those with intratumoral TLOs. The PDC tissues with intratumoral TLOs had capillaries consisting of mature endothelial cells covered by pericytes. CONCLUSIONS: Our results suggest that the presence of intratumoral TLOs represents a microenvironment that has an active immune reaction, and shows a relatively intact vascular network retained.